Masalah Sosial dalam Cerpen “Guru” Karya Putu Wijaya - Rochmansyah, Bagaskara Nur; Firdaus, Winci; Leonita, Leonita (Balai Bahasa Sumatra Barat, 2024)
This research aims to describe the social problems in the short story